Unfolding the recipes for conflict resolution during the new service development effort - Gounaris, Spiros; Chatzipanagiotou, Kalliopi; Boukis, Achilleas; Perks, Helen (Elsevier, 2016)
The management of conflicts that emerge during new service development (NSD) has escaped the attention of scholars. Yet differing conflict management styles (CMS) of team members and dynamics within the team create a complex managerial challenge. Additionally, the broader literature on conflict resolution shows contradictory findings preventing a clear roadmap for practitioner use when such conflicts emerge. This study draws on complexity theory and employs fuzzy set qualitative comparative analysis, drawing on data from 543 members of 116 NSD projects, to unravel conflict resolution recipes. The results reveal, in detail, the variety of causal patterns that explain the linkages between individual CMS, the dynamics of the team, and two critical conflict characteristics: conflict intensity and frequency. Implications for theory and practice are identified and discussed.